Effect of fruit weight on the internal browning and quality of pineapple cv. Smooth Cayenne III- Internal browning, total soluble solids, total titrable acidity, pH, and sugars - Botrel, Neide; de Carvalho, Vânia Déa (Pesquisa Agropecuaria Brasileira, 1993)
This study aimed to determine the effect of pineapple fruit weight cv. Smooth Cayenne on its chemical composition and on the internal browning rate as well as to evaluate chemical composition alteration after storage with and without refrigeration. Fruits came from Ijaci county, MG, Brazil. The experimental design was completely randomized in a 2 x 6 factorial scheme, where six weight classes (P1 – 1,800 to 2,300g, P2 – 1,500 to 1,799g, P3 – 1,300 to 1,499g, P4 – 1,100 to 1,299g, P5 - 900 to 1,099g, and P6 - 700 to 899g) and two storage processes (with and without refrigeration) were studied. The following evaluations were done: internal browning, total titrable acidity, pH, total soluble solids and sugars (total, reducing and non-reducing). The larger fruits were more susceptible to internal browning (P1 and P2) which presented greatest amount of total soluble solids and highest total acidity rate. Refrigerated ripe fruits showed lower amounts of total soluble solids, total titrable acidity, sugars (total, non-reducing) and greater amounts of pH, total soluble solids rate, total titrable acidity, and reducing sugars.